Notes on money as technology - Raúl A. Carrillo (Levy Economics Institute of Bard College, 2024)
Scholars and affiliates of the Levy Economics Institute have long demonstrated a granular understanding of the "operations" of money, which entails understanding the financial system's law and technology (Grey 2019, Tymoigne 2014, Fullwiler 2010, Bell and Wray 2002-3, Bell 2000). During the dot-com bubble, many Levy-affiliated economists underscored the relationship between government fiscal surpluses and unsustainable private debt (Godley and Wray 1999). Recently, scholars have written about the collapse of Silicon Valley Bank (Grey 2023; Tankus 2023) and resurgent speculation in the tech sector (Veneroso and Pasquali 2021). These are but a few examples. Here, I present some brief thoughts on money as a technology-money itself. I argue there is value in thinking of money not only as a legal institution, political, economic, or social relation but as technology. The exercise sharpens our vision of the future of money even as we continue to believe in radical uncertainty. I address a few points in this essay. First, I make the case for money as technology. I then survey three applications: 1) the trajectory of state money as a technology of public finance and its relationship to the suppression of indigenous and non-state monies, 2) the regulation of moneylike liabilities issued by technology companies, which operate according to the accumulative logic of Silicon Valley rather than Wall Street, and 3) money's future as a technology of surveillance, discipline, and punishment. Finally, I call for scholarship to inform a vision of money as a more democratic technology (per the mission of the Economic Democracy Initiative and Levy Economics Institute).
Keywords: 330; Money; Technology; Neochartalism; Privacy; Surveillance; De-monetization